STAGE-DEPENDENT IMMUNOPATHOGENETIC FEATURES OF ACUTE NONLYMPHOBLASTIC AND ACUTE LYMPHOBLASTIC LEUKEMIA - O. V. Smirnova; A. A. Savchenko; V. T. Manchuk (Медицинская иммунология, 2014)
Abstract. We examined immunological state in 100 patients with acute non-lymphoblastic leukemia (ANLL, M4), and in 73 cases of acute lymphoblastic leukemia (ALL, common variant). The most expressed disturbances of immune status in ANLL patients were revealed during relapses, and in patients with ALL they were detected in the state of clinical remission. In cases of ANLL, T cell immunodeficiency did develop in crisis and remission, whereas combined T- and B-cell immunodeficiency occurs during relapse of ANLL. T cell immunodeficiency was found to develop at all stages of ALL. These changes and differences may characterize specific immunopathogenetic aspects of development and progression of ANLL and acute ALL.